Resiko Obesitas Berdasarkan Perubahan Kebiasaan Makan dan Aktifitas Fisik Remaja Putri Selama Pandemi Covid-19 - Testcia Arifin; Susmiati Susmiati; Deswita Deswita (FORIKES, 2022)
One of the issues of concern to the government in Indonesia is nutritional status. The Covid-19 pandemic has changed eating habits and physical activity patterns, putting them at risk for obesity. This study aims to compare the risk of obesity before and during the pandemic based on eating habits and physical activity of young women. This research method was a comparative study with a population of young women and a sample of 190 people by means of sampling, namely purposive sampling. The method of collecting nutritional status data was measuring body weight and eating behavior questionnaires and physical activity using the Physical Activity Questionnaire-Adolescent (PAQ-A). The results of the study showed that there had been a change in eating habits during the Covid-19 pandemic in a better direction in the dimensions of eating regularity, breakfast, fruit consumption and eating with family. The frequency of consuming fried food during a pandemic had the risk of causing obesity during a pandemic, while other eating habits did not pose a risk of obesity before and during the Covid-19 pandemic. Physical activity was a protective factor against obesity during the Covid-19 pandemic, with OR = 0.135 and p value <0.05. Intervention regarding behavior change is urgently needed to address the problem of obesity during a pandemic.Keywords: physical activity; Covid-19; eating habit; obesity ABSTRAK Salah satu masalah yang menjadi perhatian bagi pemerintaham di Indonesia adalah status gizi. Pandemi Covid-19 mengubah pola kebiasaan makan dan aktivitas fisik, sehingga berisiko terhadap terjadinya obesitas. Penelitian ini bertujuan untuk mengetahui perbandingan resiko obesitas pada sebelum dan saat pandemi berdasarkan kebiasaan makan dan aktivitas fisik remaja putri. Metode penelitian ini adalah comparative study dengan populasi remaja putri dan sampel sebesar 190 orang dengan cara pengambilan sampel yaitu purposive sampling. Cara pengumpulan data status gizi adalah pengukuran berat badan dan kuesioner kebiasaan makan (Eating behavior questionnaire) serta aktivitas fisik dengan Physical Activity Questionnaire-Adolescent (PAQ-A). Hasil penelitian menunjukkan terjadinya perubahan kebiasaan makan selama pandemi Covid-19 ke arah lebih baik dalam dimensi keteraturan makan, sarapan pagi, konsumsi buah dan makan dengan keluarga. Frekuensi konsumsi gorengan saat pandemi berisiko menimbulkan obesitas selama pandemi, sedangkan kebiasaan makan lainnya tidak memiliki risiko obesitas sebelum dan selama pandemi Covid-19. Aktifitas fisik merupakan faktor protektif terhadap kejadian obesitas selama pandemi Covid-19, dengan OR = 0,135 dan nilai p <0,05. Intervensi tentang perubahan perilaku sangat diperlukan untuk mengatasi masalah obesitas selama pandemi.Kata kunci: aktivitas fisik; Covid-19; kebiasaan makan; obesitas